Examining the relationship between strategic HRM and hospital employees' work attitudes: an analysis across occupational groups in public and private hospitals. Issue 5 (9th March 2019) - Oppel, Eva-Maria; Winter, Vera; Schreyögg, Jonas
Abstract: As human resource challenges have increased, strategic human resource management (SHRM) in hospitals has evolved into an important management task. Accompanying its growing relevance, there is an evolving research stream on the impact of SHRM on organizational and individual-level outcomes in the hospital context. We aim to address two remaining research gaps by investigating variations in the use of SHRM across organizations (public vs. private ownership types) and differences in the relationship between SHRM and employee attitudes within organizations (for the occupational groups of nurses and physicians). This study is based on a sample of 179 German acute care hospitals. We employ ANOVA and logistic regression analyses, and our results corroborate previous research findings showing that SHRM has positive effects on employee attitudes. However, the effects vary in significance and magnitude, depending on whether nurses or physicians are targets. Further, we reveal significant SHRM differences in public- vs. private-sector organizations.